A Note on Public Goods: Non-Excludability Implies Joint Consumability - Thomas Christiaans (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1998)
While there are various definitions of public goods, the property of joint consumability has become the main or sole defining characteristic of such goods. Among the other characteristics the property of non-excludability is the one primarily discussed. While it is common in the literature to assert that the latter characteristic is neither necessary nor sufficient for the first to hold, it is shown in the present paper that a reasonable definition of non-excludability implies joint consumability, at least in the framework of the usual timeless and spaceless neoclassical model. Moreover, it is argued that this special case bears some importance for more realistic models involving public goods
Keywords: 330; Öffentliche Güter; Definition; Theorie